Second-hand emotion?: exploring the contagion and impact of trauma and distress in the asylum law context - Baillot, Helen; Cowen, Sharon; Munro, Vanessa (Wiley, 2013)
Applicants' accounts of experiences of fear, trauma, violence, and persecution are central to the process of claiming asylum. These narratives are, at a human level, primed to provoke emotional responses, not only in the narrator but also in those to whom the account is relayed. In this article, we explore the vectors of emotionality that permeate asylum decision-making in the United Kingdom, focusing particularly on the risk faced by the professionals involved of suffering vicarious trauma.